Get Answers to all your Questions

header-bg qa

\vec{a}\, \, and \, \, \vec{b} such that \vec{a}-\vec{b}=\hat{i}-\hat{j}+\hat{k},(-\vec{b})=\hat{i} then \vec{a} equals

Option: 1

-\hat{j}-\hat{k}


Option: 2

-\hat{j}+\hat{k}


Option: 3

\hat{j}+\hat{k}


Option: 4

\hat{j}-\hat{k}


Answers (1)

best_answer

As we learned

Difference of two vectors -

\vec{a}+\left ( -\vec{b} \right )=\vec{a}-\vec{b}

- wherein

The difference of two vectors is same as the sum of one vector and negative of other vector

 

 \vec{a}-\vec{b}=\vec{a}+(-\vec{b})

\Rightarrow \hat{i}-\hat{j}+\hat{k}=\vec{a}+\hat{i}

\Rightarrow \vec{a}=-\hat{j}+\hat{k}

So, option(B)

 

Posted by

Divya Prakash Singh

View full answer

JEE Main high-scoring chapters and topics

Study 40% syllabus and score up to 100% marks in JEE

Similar Questions